Lipid profile and blood glucose in patients with Diabetes Mellitus treated with Cinnamon - Systematic Review and Meta-analysis with randomized clinical research (Research, Society and Development, 2021)
This study aimed to measure the efficiency of cinnamon in patients with Type 2 Diabetes Mellitus (DM2), comparing fasting plasma glucose averages and lipid profiles with a placebo group through a meta-analysis. Four databases were the source of the research to find the articles used, including: Medline / PubMed, LILACS and NCBI. 11 randomized clinical trials that evaluated cinnamon on glycemic and lipid parameters were included in this study. Meta-analysis was performed with the aid of the STATA® 16.0 software, which determined the difference in glucose means and lipid profiles compared to a placebo group. Cinnamon at concentrations of 250 mg twice a day decreased blood glucose with MD = -0.25 (95%CI = - 0.36 to -0.14; p